Workforce Experience and Retention in Nursing in Australia - Dockery, A.M. (My University, 2004)
The labour market for nurses appears to be persistently in a state of shortage, as evidenced by regular reports of “the nursing crisis”. This paper draws on data from two surveys to investigate critical aspects of the working lives of Australian nurses: a survey of Registered Nurses in Western Australia and the nationally representative Household Income and Labour Dynamics Australia survey. While nurses face strong employment opportunity, consistent with an occupational shortage, there is evidence of widespread dissatisfaction on other aspects of their jobs. Despite strong dissatisfaction with pay, estimated wage equations suggest that, by and large, nurses’ pay is in line with that of other women when other factors are controlled for. Dissatisfaction with non-pay aspects of the job appears to have a stronger influence on overall job satisfaction and on intentions to leave the profession. The age profile and future intentions of the current nurse workforce suggests a continuing, if not worsening, shortage of qualified nurses in Australia.
Working Paper Women's Economic Policy Analysis Unit, Curtin Business School
Keywords: Employment; Employment -- Occupations and careers; Labour market; Employment and unemployment